Palladium nanoparticles as reusable catalyst for the synthesis of N-aryl sulfonamides under mild reaction conditions. (3rd March 2016) - Khalaj, Mehdi; Ghazanfarpour-Darjani, Majid; Talei Bavil Olyai, Mohamad Reza; Shamami, Sakineh Faraji
Abstract : An efficient palladium nanoparticles-catalyzed N -arylation of sulfonamides and sulfonyl azides is described. This procedure serves as an active protocol for intermolecular C–N bond formation using Pd(OAc)2 in PEG-400 under air. Aryl bromides and triflates react at 35°C, while aryl chlorides require heating to 50°C and give the desired products only in low yields. This reaction proceeds smoothly in acceptable yields using low catalyst loading. GRAPHICAL ABSTRACT: